The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0103-64402009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of tubular diameter and quantity for human and bovine dentin at different depths

Abstract: This study compared the tubular dimensions and distribution of human and bovine dentin. Ten human molars and 10 bovine incisors were ground with a high-speed handpiece to obtain 3 sections at different dentin depths (superficial, middle and deep). The specimens were sputter-coated with gold to be examined under scanning electron microscopy (SEM). Three SEM micrographs were recorded randomly for each dentin depth. The number of tubules was counted and the diameter of 5 tubules selected at random was measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 17 publications
3
65
0
Order By: Relevance
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
“…No significant difference was found in the number of open dentin tubules in either species. In contrast, Lopes et al (26) compared the tubular dimensions and distribution of human and bovine dentin in superficial, middle and deep dentin regions. The authors found that the number of tubules per square millimeter, regardless of the region, was significantly higher in human dentin than in bovine dentin.…”
Section: Micro-morphology Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In human tooth DT diameters are approximately 0.9 µm at the DEJ and 2.5 µm at the surface facing a dental pulp where DT are also packed closer together [4]. Similarly, diameters of DT decrease towards the external layers of dentin in some animals (in canine teeth from 2.1 µm to 0.9 µm [5,6] and in equine teeth from 2.5 µm to 1.0 µm) [3], while in bovine teeth DT diameters are narrower at the dentin surface facing a pulp comparing to those at the periphery [7,8] (with main DT diameters measuring 1.8 µm at a pulp side and 2.3 µm at DEJ) [7].…”
Section: Introductionmentioning
confidence: 96%
“…In studies focusing adhesion to enamel and dentine bovine incisors are commonly employed as a substitute to human teeth [28,29], since they are larger and are easily obtained. Nevertheless, the use of bovine dentin in such studies is being questioned due to different microstructural characteristics [7,8] which significantly affect the strength of the adhesive bonds created among restorative materials and dentin [30]. The aim of the study was, first of all to determine variations in microstructure of porcine, canine, equine and human dentin as analysed by scanning electron microscope (SEM).…”
Section: Introductionmentioning
confidence: 99%